KEMAMPUAN KESADARAN FONOLOGIS SISWA BERKESULITAN MEMBACA - Nurhaq, Hana Mumtazia; Mulyati, Yeti; Rahma, Rosita (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2020)
This research was aimed to obtain a view of phonological awareness of childrenreading difficulty. This view was collected through interviews and phonologicalawareness tests with instruments adapted from the Phonological Awareness Test(Robertson and Salter, 1997). The participant was a third grade of Junior HighSchool student in Bandung who had difficulty in reading. This research used aqualitative approach with a case study method. The results showed that: 1) rhymingskills of 42.5%; 2) segmenting skills of 30%; 3) isolation skills of 0%; 4) removingskills of 10%; 5) replacing skills of 0%; and 6) combining skills of 27.5%. Theseresults can be useful as initial information for the preparation of phonologicalawareness training intervention programs for students with reading difficulty. Thisinitial information is needed so that the intervention is designed to be right ontarget and in accordance with the needs of students with reading difficulties.